Antibacterial and antioxidant activities of acid and bile resistant strains of Lactobacillus fermentum isolated from miang - Srikanjana Klayraung (2018)
Miang is a kind of traditional fermented tea leaves, widely consumed in northern Thailand as a snack. It contains several kinds of Lactobacilli spp. The aim of this study was to isolate strains of Lactobacillus fermentum from miang and to investigate their antibacterial and antioxidant activities. The agar spot and well assays were used for determination of antibacterial power. The antibacterial mechanism was investigated by cell morphologic change under scanning electron microscope (SEM). Antioxidant activity was studied by means of free radical scavenging and ferric reducing power assays. The acid and bile screening tests indicated that L. fermentum FTL2311 and L. fermentum FTL10BR presented antibacterial activity against several pathogenic bacteria: Listeria monocytogenes DMST 17303, Salmonella Typhi DMST 5784, Shigella sonnei DMST 561 (ATCC 11060) and Staphylococcus aureus subsp. aureus DMST 6512 (ATCC 6538Ptm). The results from SEM suggested that the antibacterial action was due to the destruction of cell membrane which consequently caused the pathogenic cell shrinking or cracking. The antioxidant study suggested that both L. fermentum FTL2311 and L. fermentum FTL10BR strains could liberate certain substances that possessed antioxidant activity expressed as trolox equivalent antioxidant capacity (TEAC) and equivalent concentration (EC) values for free radical scavenging and reducing mechanisms, respectively. The supernatant of L. fermentum FTL2311 broth revealed TEAC and EC values of 22.54±0.12 and 20.63±0.17 μM.mg-1respectively, whereas that of L. fermentum FTL10BR yielded TEAC and EC values of 24.09±0.12 and 21.26±0.17 μM.mg-1respectively. These two strains isolated from miang present high potential as promising health-promoting probiotics.